Teaching and learning strategies for sustainable development - Sengupta, Enakshi; Blessinger, Patrick; Yamin, Taisir Subhi (Emerald Publishing Limited, 2020)
The United Nations Sustainable Development Goals challenges us all to promote sustainable development. Higher education is a key arena for educating students in sustainability and sustainable developments, and for producing research on these key issues. This timely book explores the sustainable development goals, how well universities have been able to integrate them into their curriculum, and how universities can institutionalize the goals and sustainable development into their strategic plans and institutional culture. Authors from Nigeria, sub Saharan Africa, Italy and the Middle East explore how to achieve these targets in the face of shifting expectations.
Includes index.
Keywords: Sustainable development -- Study and teaching.; Business & Economics -- Development -- Sustainable Development.; Sustainability.; elektronické knihy; electronic books